Phenotypic and Genetic Characterization of Antimicrobial Profiles of Helicobacter pylori Strains in Cuba - Llanes, Rafael; Soria, Claudia; Nagashima, Shigeo; Kobayashi, Nobumichi; Gala, Angela; Guzmán, Daymi; Feliciano, Onelkis; Valdés, Lidunka; Gutiérrez, Oderay; Fernández, Heriberto; Llop, Alina; Wada, Akihiro (Journal of Health, Population and Nutrition, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The study evaluated the antibiotic resistance patterns of Helicobacter pylori strains against metronidazole and clarithromycin in a hospital in Havana, Cuba. Eighty-five percent, 22.5%, and 10% of 40 H. pylori strains investigated were resistant to metronidazole, ciprofloxacin, and clarithromycin respectively but all were susceptible to amoxicillin and tetracycline. RdxA truncation was found only in metronidazole-resistant strains. In such strains, reported are eight and two novel mutations in the rdxA and frxA genes respectively. Two-point mutations in the 23S rRNA genes of clarithromycin-resistant strains were detected. A high prevalence of metronidazole resistance was found in Cuban H. pylori strains. Mutations in the rdxA gene may contribute more significantly than frxA gene to the high level of resistance to metronidazole. This study supports the need to continue monitoring the antibiotic susceptibility in H. pylori in Cuba to guide the treatment of such infection. Key words: Antibiotic resistance; Gene mutations; Helicobacter pylori; Cuba DOI: 10.3329/jhpn.v28i2.4881 J Health Popul Nutr 2010 Apr; 28(2): 124-129